Young minds, young wonders - Abd Razak, Dzulkifli (2007)
"London of course has its significance to Malaysia's independence. It was right here that Tunku Abdul Rahman, Tun VT. Sambanthan and Tun H.S. Lee started their fight and struggles for the nation's independence. "Fifty years later, today in the same place, we gather to give meaning to that independence. We are here to examine ourselves whether as a nation we have managed to fulfil the true meaning of independence. " THESE were the words of a future leader as she introduced an impressive initiative recently. Qurratul Ain Zainul, the project director, was one of the many able, young and passionate organisers who gave their fullest to a project called "Projek Amanat Negara IV", or PAN IV.